Strategic public–private arrangements enhance accelerators’ access to climate smart agriculture (CSA) and climate information services (CIS); Ghana scaling model - Tepa Yotto, Ghislian; Obeng Adomaa, Faustina; Dalaa, Mustapha Alasan (2025)
This InfoNotes summarises AICCRA partners access to CSA and CIS. It highlights their capacities strengthened to scale innovations across four thematic bundles – smart production and soils bundle, solar irrigation for female farmers, smart seed packs and market systems and climate smart IPM.